A Thematic Analysis of Pharmacy Students’ Experiences of the Undergraduate Pharmacy Degree in Ireland and the Role of Mindfulness - O’Driscoll, Michelle (Am J Pharm Educ, 2019)
Objective. To determine pharmacy students’ experiences of stress as part of the current pharmacy degree, and to explore the potential of incorporating the principles of mindfulness into course work in the undergraduate degree. Methods. Undergraduate pharmacy students from the five pharmacy schools in Ireland were invited to participate in focus groups between February and November 2016. Recruitment occurred via emails sent by a school’s academic or administrative member. Focus groups were audio recorded, anonymized and transcribed by the corresponding author. Transcripts were analyzed using the Braun and Clarke method of thematic analysis and coded. Results. Twenty pharmacy students (60% female) representing all years of study from three of the five pharmacy schools participated across five focus groups. The five key themes that emerged were: so much to do, so little time; the role of lecturers; we are smart people, we want to do well; learning by doing; and mindfulness as a coping tool. Conclusion. The findings of this study support the hypothesis that students experience stress and would welcome mindfulness-based interventions as a management option in the degree. Specifically, the emphasis that mindfulness places on experiential learning would be well-received by students.